2020
DOI: 10.1002/wdev.396
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell RNA sequencing in Drosophila: Technologies and applications

Abstract: Single‐cell RNA sequencing (scRNA‐seq) has emerged as a powerful tool for investigating cell states and functions at the single‐cell level. It has greatly revolutionized transcriptomic studies in many life science research fields, such as neurobiology, immunology, and developmental biology. With the fast development of both experimental platforms and bioinformatics approaches over the past decade, scRNA‐seq is becoming economically feasible and experimentally practical for many biomedical laboratories. Drosoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 156 publications
(242 reference statements)
0
51
0
Order By: Relevance
“…When we visualized 24h APF transcriptomes in the t-SNE space (van der Maaten & Hinton, 2008) following dimensionality reduction with 500 over-dispersed genes from this stage, 24h APF transcriptomes separated into three distinct groups instead of forming clusters corresponding to each neuron type (Figure 4-supplement 1A). Upon querying expression of transcripts known to be expressed in ORNs such as acj6, a transcription factor that is ubiquitously expressed at 42h APF (Li et al, 2020), we found that acj6 was enriched in the largest cluster but was absent from the other two clusters (Figure 4-supplement 1B). We asked if Acj6 protein reflected its transcript expression in the 24h APF antenna by co-immunolabeling with Acj6 and the pan-neuronal marker Elav.…”
Section: Mapping 24h Apf Transcriptomic Clusters To Their Glomerular mentioning
confidence: 99%
See 2 more Smart Citations
“…When we visualized 24h APF transcriptomes in the t-SNE space (van der Maaten & Hinton, 2008) following dimensionality reduction with 500 over-dispersed genes from this stage, 24h APF transcriptomes separated into three distinct groups instead of forming clusters corresponding to each neuron type (Figure 4-supplement 1A). Upon querying expression of transcripts known to be expressed in ORNs such as acj6, a transcription factor that is ubiquitously expressed at 42h APF (Li et al, 2020), we found that acj6 was enriched in the largest cluster but was absent from the other two clusters (Figure 4-supplement 1B). We asked if Acj6 protein reflected its transcript expression in the 24h APF antenna by co-immunolabeling with Acj6 and the pan-neuronal marker Elav.…”
Section: Mapping 24h Apf Transcriptomic Clusters To Their Glomerular mentioning
confidence: 99%
“…Single-cell transcriptomics is a powerful tool for the discovery of novel cell types, revealing subtype specific markers, and studying gene expression changes underlying cellular development and maturation (Li, 2020). Adult ORNs, like many insect tissues, are tightly associated with the hardened exoskeleton and are difficult to isolate using standard cell dissociation protocols.…”
Section: Single-nucleus Rna-seq Can Be Used To Profile Cuticle-associmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-cell RNA sequencing (scRNA-seq) is a powerful tool to investigate the mechanisms underlying nervous system development and function ( Ofengeim et al, 2017 ; Mu et al, 2019 ; Li, 2020 ). Recent scRNA-seq studies in the Drosophila nervous system have enabled the discovery of new cell types, mechanisms important for development and aging, and genes controlling neural specification and wiring ( Li et al, 2017 ; Croset et al, 2018 ; Davie et al, 2018 ; Brunet Avalos et al, 2019 ; Allen et al, 2020 ; Kurmangaliyev et al, 2020 ; Özel et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This information can help us obtain a more complete picture of both known and unexplored pathways underlying neural development and function. Recently, the advent of single-cell RNA sequencing (scRNA-seq) has paved the way toward obtaining such data ( Li et al, 2017 ; Kalish et al, 2018 ; Zhong et al, 2018 ; Li, 2020 ). Here, we profiled and analyzed the single-cell transcriptomes of most uniglomerular excitatory PNs.…”
Section: Introductionmentioning
confidence: 99%